2005
DOI: 10.1021/ie050901m
|View full text |Cite
|
Sign up to set email alerts
|

Oxidation of Aliphatic and Aromatic Sulfides Using Sulfuric Acid

Abstract: Sulfuric acid is proposed as an inexpensive oxidant for use in the oxidative desulfurization (ODS) of petroleum. The oxidative extraction of thiophene, tetrahydrothiophene, and dibutyl sulfide by concentrated sulfuric acid in a two-liquid-phase reactor is demonstrated. The reaction proceeds rapidly at room temperature at sulfide concentrations greater than ∼100 ppm S and yields sulfoxides, sulfonates, and other oxidized sulfur species as products. The oxidized sulfur species are effectively extracted into the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 13 publications
0
10
0
Order By: Relevance
“…Sulfuric acid and SO 3 , on the other hand, has been reported to be able to oxidize thiophenes at elevated temperatures, itself being reduced to H 2 SO 3 or SO 2 , respectively. 26,27 For SO 3 and TTh:…”
Section: Resultsmentioning
confidence: 99%
“…Sulfuric acid and SO 3 , on the other hand, has been reported to be able to oxidize thiophenes at elevated temperatures, itself being reduced to H 2 SO 3 or SO 2 , respectively. 26,27 For SO 3 and TTh:…”
Section: Resultsmentioning
confidence: 99%
“…Alcohols, the organic function present in the glucose molecule, are oxidized to ethers under action of this acid and heating (Solomons and Fryhle, 2001). In addition, Nehlsen et al (2006) found synergism between sulfuric acid and heating as oxidizing agents of aliphatic and aromatic sulfides, reducing the Gibbs free energy value for these reactions.…”
Section: Spectrophotometric Alternatives For Embrapa and Walkley-blacmentioning
confidence: 99%
“…Oxidation of sulfides is a direct method to synthesize sulfoxides which play important roles in pharmaceutical, biologically active compounds, organic synthesis, and solvent extraction, etc. Numerous studies about the oxidation of sulfides have been done over the years. Aqueous H 2 O 2 is considered as an excellent oxidant for the oxidation of sulfides because it is cheap, efficient, highly chemoselective, and environmentally friendly. Oxidation of sulfides with aqueous H 2 O 2 is a heterogeneous liquid–liquid reaction because of the immiscibility of organic sulfides and aqueous H 2 O 2 . In order to enhance the mass transfer between the two phases, organic solvents are always used. , The organic solvents used in the process are usually toxic and environmentally hazardous, which limit its scale-up.…”
Section: Introductionmentioning
confidence: 99%